Ka'aNIB : a research and development complex for Philippine Coconut Industry - Coralde, Mary Ann P. (Manila : National University, 2018)
The coconut industry is a resilient one, full of potential but has many weaknesses. While it hosts many opportunities, it also faces many threats and problem.
Chapter 1. The problem and its setting -- Chapter 2. Review of Related literature -- Chapter 3. Research methodology -- Chapter 4. Data gathering, collation and analysis data -- Chapter 5. Design development -- Chapter 6. Translation.
Includes bibliographical references.
Keywords: COCONUT INDUSTRY; COMPLEX -- PLANNING